(untitled) (Global Journal of Science Frontier Research, 2019)
The study was carried out on proximate and mineral analysis of water melon sold at North bank market Makurdi. Water melon samples were purchased at North bank in January, 2018. The samples were sliced using a knife to separate the seeds, pulp and rind. These samples were dried and milled into powder and were analyzed for proximate and mineral content using standard methods and atomic absorption spectrophotometer (AAS). The results for the proximate analysis revealed the presence of moisture content ranging from 3.50 % to 10.90 %, ash content (2.80 % to 6.50 %), fibre content (5.80% to 15.30%), crude fat (0.40 % to 13.10 %), crude protein (3.20 % to 19.20 %) and carbohydrate (46.10 % to 75.50 %). The result obtained from the mineral analysis revealed the presence of selected element, with Calcium having the highest mean value (25.69 mg/100g), followed by Magnesium (3.60 mg/100g), Iron (0.22 mg/100g) and Chromium (0.11 mg/100g), there were no traces of Lead and Cadmium. The data (result) of the study showed that the proximate and mineral parameter with the exception Pb and Cd were present in the bark, pulp and seeds although their concentration in the rind, seed and pulp vary significantly and also fall below the WHO recommended standard for minerals element.